Different roles of personas. - Abd Malik, Sofianiza; Edwards, Alistair (IIUM Press, 2011)
Personas can be used in a variety of ways. The use of personas is explored in different contexts such as a tool for requirements elicitation, marketing purposes and development application for museum/gallery visitor